Legislative Efficiency and Political Inclusiveness: The Effect of Procedures on Interest Group Mobilization in the European Parliament. Issue 2 (3rd April 2019) - Coen, David; Katsaitis, Alexander
ABSTRACT: This paper contributes to discussions surrounding interest group representation in the European Parliament. Drawing from conceptualizations of legitimacy, and theoretical work on information-access we argue that different procedures bestow a different type of authority to parliamentary committees affecting their legitimacy orientation, in turn impacting the balance between private and public interests mobilised. We assess a population of 10, 000 accredited lobbyists, and the procedural output across the 7th legislature's committees (2009–2014). Our analysis indicates that committees with a higher ratio of Ordinary Legislative Procedures to Own Initiative Reports see greater private interest mobilisation. Conversely, in committees where the procedures' ratios are inverse we observe greater public interest mobilisation. Theoretically, we provide a novel approach for framing the committee's nature from a procedural perspective, bridging discussions on interest group mobilisation and the democratic deficit. Empirically, the results overturn the premise of business dominance across the institution's committees through a unique dataset.